2021
DOI: 10.1097/ajp.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of the Brief Pain Inventory-Short Form (BPI-SF) and Revised Short McGill Pain Questionnaire Version-2 (SF-MPQ-2) in Pain-related Musculoskeletal Conditions

Abstract: Objective: The objective of this study was to systematically locate, critically appraise, and summarize clinical measurement research addressing the use of Brief Pain Inventory-Short Form (BPI-SF) and Revised Short McGill Pain Questionnaire Version-2 (SF-MPQ-2) in pain-related musculoskeletal (MSK) conditions. Materials and Methods:We systematically searched 4 databases (Medline, CINAHL, EMBASE, and SCOPUS) and screened articles to identify those reporting the psychometric properties (eg, validity, reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…The Brief Pain Inventory (BPI) is a validated and widely used inventory that is developed to assess the severity of pain and the impact of pain on daily functions (Jumbo et al, 2021 ). It is a 9-item self-administration in which the pain severity is assessed by 4 items, including the worst and least pain in the previous 24 h, pain severity on average, and pain “right now” ranging from 0 (no pain) to 10 (pain as bad as you can imagine).…”
Section: Methodsmentioning
confidence: 99%
“…The Brief Pain Inventory (BPI) is a validated and widely used inventory that is developed to assess the severity of pain and the impact of pain on daily functions (Jumbo et al, 2021 ). It is a 9-item self-administration in which the pain severity is assessed by 4 items, including the worst and least pain in the previous 24 h, pain severity on average, and pain “right now” ranging from 0 (no pain) to 10 (pain as bad as you can imagine).…”
Section: Methodsmentioning
confidence: 99%
“…Ratings of the four items are averaged to provide a BPI-SF score, or Pain Rating Index (PRI). In their review, Jumbo et al (2021) reported psychometric properties of the BPI-SF, including Cronbach's alpha coefficients of .82 to .96 for internal consistency and intraclass correlation coefficients of .90 for total score reproducibility and .73 to .90 for the subscale scores.…”
Section: Methodsmentioning
confidence: 99%
“…The BPI was designed to assess the severity of physical pain and the impact of pain on daily functioning [ 25 ]. The instrument has been used in a number of clinical settings and is shown to be valid and reliable (internal consistency α values ranged from 0.83 to 0.96) [ 26 ]. We assessed a single measure, rated 0–10, which asked how often pain interfered with the respondents’ relationships with people in the past week as a negative indicator of social functioning.…”
Section: Methodsmentioning
confidence: 99%